2021
DOI: 10.3390/en14133984
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Impact of Wind Power Generation on a Local Community: Economics Analysis of Subjective Well-Being Data in Chōshi City

Abstract: In this study, we analyzed the external effects of wind turbines, which are often considered detrimental to the promotion of wind power generation. Understanding these externalities is essential to reaching a consensus with residents who live near the site of a planned wind turbine. Our research objective was to determine the relationship between wind turbines and people’s well-being in areas where they have been installed for a long time. We hypothesized that wind turbines would have a negative impact on peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Obviously, there are various interpretations of green policymaking in local governments. Green policymaking in Japanese municipalities can focus on GPP [14] as presented in Section 2.1, but also on urban regeneration [16], renewable energy [17], emissions [18], public transport [19], and bicycle planning [20], to mention a few. Therefore, it is important to discuss local green policymaking as interpreted within the scope of this study.…”
Section: Green Policymaking In Japanese Municipalitiesmentioning
confidence: 99%
“…Obviously, there are various interpretations of green policymaking in local governments. Green policymaking in Japanese municipalities can focus on GPP [14] as presented in Section 2.1, but also on urban regeneration [16], renewable energy [17], emissions [18], public transport [19], and bicycle planning [20], to mention a few. Therefore, it is important to discuss local green policymaking as interpreted within the scope of this study.…”
Section: Green Policymaking In Japanese Municipalitiesmentioning
confidence: 99%
“…Studies on the relationship between nature and SWB have demonstrated that green spaces and waterfront areas positively correlate with SWB and physical and mental health [14][15][16][17]. However, the relationship of Japanese people with nature may be related to the smaller unexplained residuals and, thus, lower levels of happiness.…”
Section: Introductionmentioning
confidence: 99%